Smart Canteen System for Nepalese Institutions Using ESP32 and NFC: A Low-Cost IoT Approach - Adhikari, Prajjwal; Thapaliya, Sudeep (Journal of UTEC Engineering Management, 2025)
The institutional canteens that operate in the traditional way often have a lot of operational inefficiency such as long queues, human errors during the Billing and the manual nature of the transaction process. The present paper explains the designing process and prototyping of a Smart Canteen Payment System, answering the questions regarding the use of low-cost IoT solutions, including the ESP32 microcontroller and PN532 NFC module. The system integrates hardware with a locally running web-based application for the purpose of easy identification of users, payment processing, and the real-time sales monitoring. The prototype cuts out the manual interaction, enhances accuracy of the transactions and provides dynamic menu and user management due to overcoming the limitations of the current systems: semi-automated systems. Controlled tests performed in the form of functional tests proved its ability to reduce errors and stimulate quicker service. Large-scale deployment and longitudinal testing have yet to be carried out, but there is a clear potential demonstrated by the system in being deployed on a larger-scale in resource-limited institutional environments such as Nepal. Thus, the present paper provides an effective prototype of redesigning the campus canteen service with smart, contactless alternatives.